The impact of the wilson administration on economic crime rates - Chamlin, Mitchell B. (Journal of quantitative criminology, 1991)
Previous research, based upon the interrupted time-series analysis of monthly data, has demonstrated that changes in the organizational structure of police departments produce short-term changes in the level of reported crime. The present study extends this literature by examining the independent effects of a change in hierarchical control (i.e., the appointment of O. W. Wilson as the new chief of the Chicago Police Department) and changes, over time, in the ecological structure of Chicago on reported rates of economic crime. The multivariate analyses indicate that the failure to take into account organizational change leads to model specification error. We conclude that longitudinal, within-jurisdictional research, based on the analysis of UCR data, must take into account changes in police bureaucracies that can affect the production of official counts of crime.